A Netnographic Analysis of ASMR Consumption on YouTube Among Individuals with Sleep and Anxiety Disorders - Triani, Yulia; Kamil, Ade Ikhsan; Arifin, Awaludin; Chalid, Ibrahim; Fitri, Dwi; Aulia, Faizul Aulia (Jurnal Ilmiah Guru Madrasah, 2025)
Autonomous Sensory Meridian Response (ASMR) content has become increasingly prevalent on digital platforms, particularly YouTube, and is often utilized by individuals seeking relief from sleep and anxiety disorders. This study employs a qualitative netnographic approach to examine the patterns, motivations, and perceived effects of ASMR consumption among individuals coping with insomnia and anxiety. Data were collected through in-depth interviews with ten informants and supported by observation of user interactions within the ASMR community. The findings indicate that ASMR is commonly integrated into daily routines as a personalized strategy for relaxation and anxiety reduction, particularly before sleep. Participants reported that regular engagement with ASMR content helped them fall asleep more easily, diminished intrusive or anxious thoughts, and provided a sense of emotional comfort. However, the effectiveness of ASMR varied, with some informants experiencing significant benefits and others describing only modest or temporary relief. Social acceptance of ASMR use was also mixed, influencing whether participants chose to discuss their practices openly or keep them private. This study highlights the individualized and adaptive use of ASMR as a digital self-care tool for managing sleep and anxiety disorders. While not a substitute for professional intervention, ASMR offers an accessible and flexible resource within the broader spectrum of mental health strategies. Further research is recommended to better understand the long-term efficacy and mechanisms of ASMR, as well as its integration with traditional therapeutic approaches.